Modification of The Online Gunning Fog Index for Readability Analysis of Indonesian Texts : A Prototype Development - Mangilaleng, Juliana Tirza; Hananto, Hananto; Gea, Eklesia Khesywani (Jurnal Paedagogy, 2025)
This study aims to develop a statistical formula for the readability of Indonesian texts by modifying the Gunning Fog Index (GFI) formula. GFI is one of the objective readability statistics with a syntactic approach. The GFI formula is used to measure the readability of text based on the calculation of the number of words, sentences and complex words. The underlying theory is that a good text is a text that is appropriate or easily understood by its target readers. The level of text readability is influenced by the syntactic complexity in the text. The research method used is R&D (Research and Development). The formula is made online using Google Sheets so that the link can be accessed by the public. The developed formula uses complex word count criteria that have been adapted from the Gunning Fog Index formula. The basis of this modification is that the original GFI criteria is based on English text which is different from Indonesian text. This formula was tested using the same text sample as the text sample used by previous researchers. Data dianalisis dengan perhitungan GFI untuk jumlah kata kompleks dalam kalima. The results of this study show a more detailed difference in the Gunning Fox index. In addition, this formula provides more detailed and informative calculations that make it easier for users to analyze the readability of Indonesian texts. This study’s findings provide an improved tool for evaluating the readability of Indonesian texts, offering educators, writers, and literacy enthusiast a more accurate and accessible method to assess and enhance text comprehension for Indonesian readers.